Application of product data management technologies for enterprise integration - Gao, James X.; Aziz, Hayder; Maropoulos, Paul G.; Cheung, Wai M. (Taylor & Francis, 2003)
Product Data Management (PDM) systems and their offspring, Collaborative Product Development and Product Lifecycle Management technologies, aim to bring engineering enterprises together, allowing seamless interoperability between different departments and throughout the extended enterprises. However, there are a number of shortcomings in the current crop of commercially available systems, such as the lack of design knowledge sharing, links with Enterprise Resource Planning systems, knowledge management tools and a generic standard for PDM system implementation. This paper presents a proposed software solution to some of the above problems. In particular, the paper describes methodologies being developed that are aimed at overcoming the lack of analysable product information at the conceptual stage of product design and manufacturing evaluation, along with the integration of such a concept design tool within a distributed environment. A leading PDM system is used to manage all the information and knowledge that is made available to internet/intranet users in a controlled manner. The international standard for exchange of product data model (STEP) is implemented to enable the integration of the design environment with manufacturing and enterprise resource management systems. In addition, the paper also introduces three other recent/ongoing projects, being carried out at Cranfield University, in the application of PDM, knowledge management and STEP standard for integrated manufacturing businesses.